Detecting Cyber Crime for Forensic Computer Handling using OSINT - Salza Aulia Fitri; Muhammad Ramadhan; Raffi Ciputra; Ernis Sita Eriana; M.Irham (MultiTech Publisher, 2024)
In handling computer forensics with backward chaining, the cybercrime detection expert system serves to detect cybercrime crimes committed by criminals. Problems encountered include how to detect cybercrime crimes committed, articles that correspond to cybercrime crimes committed, and what punishment should be given to cybercrime offenders. This article provides a brief explanation of the meaning of forensics, techniques, and applications with various applications available: This expert system uses observation, interviews, and literature studies. into a system that uses hypertext preprocessor programming (PHP) and MySQL database. The design that uses HTML and CSS during the process of making this system can help in the process of detecting and handling internet violations. to supervise the forensic stove, so as to be able to find out with the type of crime committed easily and cyber crime law. The search results show that live forensic, network forensic, and mobile forensic are the most handled crimes, with a trend topic graph above 10. In contrast, computer and database forensics only have two courses.